COSMECEUTICALSâ€: AN OPINION IN THE DIRECTION OF PHARMACEUTICALS - ANURADHA S N; VILASHENE A/P GANASAN; LALITHAMBIGAI A/P JOOBI; S, Arunkumar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Cosmeceuticals are the latest addition to the health industry and are described as cosmetic products with drug-like activities. Cosmetics are products that are used to cleanse and beautify the skin (Millikan, 2001). Pharmaceuticals are essentially drug products and are defined as products that prevent, mitigate, treat or cure disease and/or affect the structure or function of the body (Vermeer and Gilchrest, 1996). Cosmeceuticals is a deliberate portmanteau of these two terms and is intended to connote drug-like benefits from an otherwise cosmetic product. While the food, drug, and cosmetic act does not recognize the term cosmeceutical,â€ the cosmetic industry has begun to use this word to refer to cosmetic products that have drug-like benefits. The term cosmeceutical was coined by Kilgman, but these lines of product became popular in 1996 and have an expanding market that has rapidly reached Africa. Many scientists and health consumers in Africa may not be conversant with this line of products. They may, therefore, be underresearched or over-utilized. In the cosmetic arena, many materials are used commercially. Cosmetic ingredients previously considered inertâ€ have the potential to provide a biologic effect to the skin. In a cosmeceutical formulation, the boundary between an activeâ€ and inertâ€ ingredient may be obscured. There is most common names of the different ingredients used in cosmeceutical products such as antioxidants, the binding agent, emollients, emulsions, humectants, lubricants, preservatives, solvents, surfactants, vehicle, etc. Potential for cosmeceutical ingredients in the United States alone is SI00 million and includes such products as skin peelers, wrinkle creams, emollients, hair growth stimulants, skin lighteners and darkeners, and botanicals. The 75 million baby boomers are the major market for cosmeceuticals. Cosmeceuticals claims are largely unsubstantiated and the term, though misleading, has probably come to stay. The term and the target consumers appear flamboyant enough to with stand Government regulations. In a free trade world, the benefits and adverse effects of cosmeceuticals are probably optimized by frequent review to inform the clinical and public stake-holders of their uses and limitations. This comprehensive review attempts to briefly, expand the recent knowledge about cosmeceuticals. Keywords: Cosmetics, Formulation/stability, Safety testing, Claim substantiation.